(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The concept of the smart cities is closely related to the opportunities of smart education that reflects how advanced technology enables learners to acquire knowledge and skills more effectively, efficiently, and conveniently. The role of smart education is to support learners in the 21st century to meet and successfully cope with the challenges of a digitalized society, including developing problem-solving skills. The aim of the paper is to examine the role of the education in modern smart cities, from the quadruple helix model perspective. Smart education has become an important strategy for building a smart society, as an essential part of the model, including collaborative innovation and interaction among government, academia, business and society. By the use of technologies and innovation, the modern educational institutions could promote not only student satisfaction with the learning process, but also support the development of sustainable smart and knowledge-based cities.